Advanced electronic security and safety system using artificial intelligence - Jalal, S. M. Shuharto; Mahamud, Md. Sajid (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.